«Machos, progres y galanes»: men and feminist movement during the seventies and eighties - Adán Gil, Carlos (Filanderas, 2019)
The article aims to immerse in the building processes of masculinities and its relationship with the feminist movement of the Radical Left in Spain during the Transition and the first years of Democracy. This article is a contribution aimed to cover a historiographic gap that threatens to bring into the present a biased discourse around the building processes of identity and the assimilation of egalitarian values.
Keywords: Masculinities; Oral history; Revolutionary left; Feminism; Identity; Gender